2006
DOI: 10.1073/pnas.0511311103
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of genetic risk for impulsivity and violence in humans

Abstract: Neurobiological factors contributing to violence in humans remain poorly understood. One approach to this question is examining allelic variation in the X-linked monoamine oxidase A (MAOA) gene, previously associated with impulsive aggression in animals and humans. Here, we have studied the impact of a common functional polymorphism in MAOA on brain structure and function assessed with MRI in a large sample of healthy human volunteers. We show that the low expression variant, associated with increased risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
470
10
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 780 publications
(531 citation statements)
references
References 50 publications
38
470
10
8
Order By: Relevance
“…Similarly to our finding, the functional response of heterozygous women carrying both high-and low-expressing allele was intermediate between homozygous female subjects. 41 This finding is consistent with a codominant effect of the alleles not only on neurobiology but on complex behavior and might be seen as supportive of a recent study showing that MAOA is among those genes that escape X inactivation. 43 Alternatively, in brain, the clonality of MAOA allele inactivation is such that mosaicism of allele expression of the heterozygotes is relatively fine-grained and the neurobehavioral phenotypes of heterozygotes are therefore intermediate.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly to our finding, the functional response of heterozygous women carrying both high-and low-expressing allele was intermediate between homozygous female subjects. 41 This finding is consistent with a codominant effect of the alleles not only on neurobiology but on complex behavior and might be seen as supportive of a recent study showing that MAOA is among those genes that escape X inactivation. 43 Alternatively, in brain, the clonality of MAOA allele inactivation is such that mosaicism of allele expression of the heterozygotes is relatively fine-grained and the neurobehavioral phenotypes of heterozygotes are therefore intermediate.…”
Section: Discussionsupporting
confidence: 88%
“…42,43 Our results showed that heterozygous individuals displayed a risk, which was intermediate between the homozygote, echoing the neuroimaging findings of Meyer-Lindenberg et al 41 Meyer-Lindenberg et al found that the genotype conferring low MAOA activity predicted amygdala hypereactivity during emotional arousal in both male subjects and female subjects. Similarly to our finding, the functional response of heterozygous women carrying both high-and low-expressing allele was intermediate between homozygous female subjects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…67 A statistical G Â E involving MAOA thus represents an important launching pad for developmental neuroscience research into the underlying causal mechanisms involved in the etiology of psychopathology. 10,64,[68][69][70] Moreover, it is possible that the MAOA gene may simply be a marker for a behavioral trait, which itself moderates the association between maltreatment and children's mental health.…”
Section: Discussionmentioning
confidence: 99%
“…A recent fMRI study shed some light on possible neurobiological underpinnings of MAOA genotype on aggressive behavior, demonstrating that the at-risk genotype results in amygdalar hyperreactivity in response to emotional arousal, paralleled by impaired response of prefrontal brain regions including the anterior cingulate cortex (Meyer-Lindenberg et al, 2006). Considering the data on reduced 5HTT availability in this structure in aggressive subjects (Frankle et al, 2005), serotonin metabolism in the cingulate gyrus seems to be a crucial determinant of disposition toward violent behavior.…”
Section: Discussionmentioning
confidence: 99%